Kesalahan terjemahan otomatis tiktok dalam akun @Ahmad Rojih - Fahmi, Ismail (Maliki Interdisciplinary Journal, 2024)
TikTok’s automatic translation feature is a computerized system used to automatically translate content from one language to another. Activating this feature will help understand content that uses a language different from the user’s language. However, in fact this feature has various limitations in the translation process. Thus, this research examines the errors found in TikTok’s auto-translation from Arabic to Indonesian through a case study on the @Ahmad Rojih account. This research aims to classify the types of TikTok automatic translation errors using the categorization provided by (Vilar et al., 2006). The method used is a qualitative descriptive method, namely using qualitative data, then analyzing it descriptively. As a result of the research, 13 data were obtained from a video entitled "A figure of merit to Shaykh Adham", found 4 types of errors, namely: 7 lexical error data, 4 disambiguation error data, 1 word order error data, and 1 unknown word error data.